ALTERNATIVE FOR PROTEIN CONCENTRATIONS OBTAINED FROM EGG WHITE BY COLD DRYING - George MOISE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper presents an alternative method to dry white eggs. Because on thermal treatment the protein denaturation is relatively high, cold drying of the white eggs maintains intact the protein chain. Eliminating the air heating from classic technology will conduct to energy reducing during the process. Also, all products, made of the white egg powder obtained using cold draying, will have complete proteins in amino acids.